Unoccupied electronic band structure of the semi-metallic Bi(111) surface probed with two-photon photoemission - Bronner, Christopher; Tegeder, Petra (Physical review. B, Condensed matter and materials physics, 2013)
While many photoemission studies have dealt with both the bulk band structure and various surface states and resonances, the unoccupied electronic structure above the Fermi level of the Bi(111) surface has not yet been measured directly although understanding of this model semi-metal is of great interest for topological insulators, spintronics, and related fields. We use angle-resolved two-photon photoemission to directly investigate the occupied and unoccupied p bands of Bi, including the bulk hole pocket at the T point, as well as the image potential states and surface states of Bi(111).
Gesehen am 08.12.2020